PENGARUH SELEBGRAM ENDORSE & ELECTRONIC WORD OF MOUTH (E-WOM ) TERHADAP MINAT BELI KONSUMEN PADA YUIKAA FASHION STORE - Nurul Hidayanti; Muhajirin; ovriyadin (Jurnal Publikasi Manajemen Informatika, 2025)
The development of digital technology has changed the way consumers interact with brands, with social media now becoming the main platform for digital marketing. Strategies such as endorsements by social media influencers and electronic word of mouth (E-WOM) have become increasingly popular approaches to building brand awareness and influencing consumer purchasing decisions. Yuikaa Fashion Store, as an online fashion industry player, has also utilized these two strategies in an effort to increase consumer interest in purchasing. However, the effectiveness of implementing these strategies still faces various challenges, such as the selection of unappealing influencers, a lack of content updates that follow trends, and negative reviews from consumers. Based on these phenomena, this study aims to analyze the influence of influencer endorsements and E-WOM on consumer purchasing interest at Yuikaa Fashion Store. The results of this study are expected to provide practical contributions to the development of digital marketing strategies and enrich academic literature on consumer behavior within the context of the online fashion industry.